2018
DOI: 10.1111/icad.12324
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term responses of darkling beetles (Coleoptera:Tenebrionidae) to the effects of fire and grazing in savannah rangeland

Abstract: Fire and grazing shape biodiversity in savannah landscapes. In land use management, knowing the effects of fire and grazing on biodiversity are important in order to ensure environmental sustainability. Beetles specifically are indicators of the biodiversity response to fire and grazing. A grazing exclusion and burning experiment in a split‐plot design was used in order to investigate the interacting effects of fire and wildlife grazing on biomass, diversity, and species composition of darkling beetles (Coleop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
5
0
1
Order By: Relevance
“…Zophosis (Halogenosis) burkei burkei (TE003 in Hering et al 2019) was described to be a niche specialist for high shrub cover on conventional cattle managed farm, where areas in high shrub cover are usually low in grass cover and food shortage (Hering et al 2019). Zophosis (Hologenosis) burkei subspecies have increased body weights in grazed conditions after fire, which refelcts their preference for simple niches (Reinhard et al 2018), supporting the idea of being indicators for conitnous wildlife grazed rangeland. Eurychora nitida and Stips dohrni, indicators for holistic management, have a flattened body shape and are slow-moving.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Zophosis (Halogenosis) burkei burkei (TE003 in Hering et al 2019) was described to be a niche specialist for high shrub cover on conventional cattle managed farm, where areas in high shrub cover are usually low in grass cover and food shortage (Hering et al 2019). Zophosis (Hologenosis) burkei subspecies have increased body weights in grazed conditions after fire, which refelcts their preference for simple niches (Reinhard et al 2018), supporting the idea of being indicators for conitnous wildlife grazed rangeland. Eurychora nitida and Stips dohrni, indicators for holistic management, have a flattened body shape and are slow-moving.…”
Section: Discussionmentioning
confidence: 92%
“…The potential of Anthiini to be incorporated into environmental monitoring programs has been recognised previously due to their close association with vegetation communities and their activity patterns being closely linked to temperature, season and rainfall (Schmidt 2001). In a previous study, we have identified the detrimental effect grazing can have on Carabidae in dry season (Reinhard et al 2018). However, information on the biology of single species is scarce and warrants greater attention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ganadería) ) y sus potenciales consecuencias negativas, como la desertificación (Figura 2.4-1, Capitulo 2) (Del Valle et al 1998;Peri et al 2016a). Estas actividades afectan la estructura de la vegetación y homogenizan el paisaje, afectando la supervivencia de muchas especies (Kaltsas et al 2012;Newbold et al 2014;Liu et al 2016;Lescano et al 2017;Reinhard et al 2019).…”
Section: Mapa De Biodiversidad Potencial Y áReas Prioritarias Para La Conservaciónunclassified